Pengembangan Smart Modul Pendidikan Agama Islam untuk Meningkatkan Keberagamaan Peserta Didik - Sriwahyuni Sriwahyuni; Martin Kustati; Nana Sepriyanti (YASIN, 2026)
The development of technology-based teaching materials has become an important need in 21st-century learning, especially in Islamic Religious Education (PAI), which is oriented not only toward mastery of knowledge but also toward the formation of students’ attitudes, worship practices, internalization of religious values, and social behavior that reflects Islamic teachings. This study aims to analyze the need for developing a SMART PAI Module, design the SMART Module, and determine its feasibility as an interactive digital teaching material to improve students’ religiosity at SMAN 1 Koto XI Tarusan. This study used a level-one Research and Development method with the 4D model, which includes the stages of define, design, development, and disseminate, with a focus on preparing a product design without testing its effectiveness. Data were collected through interviews, questionnaires, and documentation, then analyzed through a module feasibility test based on material and media aspects. The developed SMART Module was designed as an open and interactive digital teaching material that integrates PAI content, learning multimedia, practice questions, evaluation, and religious reflection features that can be accessed independently through digital devices. The results of the study are directed toward the production of a feasible SMART PAI Module design that can be used as an innovative, engaging, and interactive alternative teaching material to support the improvement of students’ religiosity. The conclusion of the study affirms that the development of the SMART PAI Module has the potential to strengthen the quality of Islamic religious learning through the integration of technology, independent learning, and reflection on religious values. The implications of this study provide practical contributions for PAI teachers and schools in developing digital teaching materials that are adaptive to the needs of 21st-century learning.